2017
DOI: 10.1186/s12886-017-0486-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of retinal nerve fibre layer and macular thickness with serum uric acid among type 2 diabetes mellitus

Abstract: BackgroundUric acid is a final breakdown product of purine catabolism in humans. It’s a potent antioxidant and can also act as a pro-oxidant that induces oxidative stress on the vascular endothelial cells, thus mediating progression of diabetic related diseases. Various epidemiological and experimental evidence suggest that uric acid has a role in the etiology of type 2 diabetes mellitus. We conducted a cross-sectional study to evaluate the correlation of retinal nerve fibre layer (RNFL) and macular thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“… 8 In addition, in a cross-sectional study of 1749 diabetic participants in Beijing, a higher SUA level was an independent protective factor for DR. 9 Moreover, a meta-analysis of nine studies and a recent study conducted in China did not demonstrate a strong association between SUA levels and DR. 18 , 19 Another study showed a poor correlation of SUA with retinal nerve fiber layer and macular thickness among T2D patients without DR or with NPDR. 20 In their study, the SUA levels of NPDR participants were significantly lower than those of participants without DR. 20 In our study sample, however, no significant difference was observed in SUA levels between patients with sub-VTDR and no DR.…”
Section: Discussionmentioning
confidence: 82%
“… 8 In addition, in a cross-sectional study of 1749 diabetic participants in Beijing, a higher SUA level was an independent protective factor for DR. 9 Moreover, a meta-analysis of nine studies and a recent study conducted in China did not demonstrate a strong association between SUA levels and DR. 18 , 19 Another study showed a poor correlation of SUA with retinal nerve fiber layer and macular thickness among T2D patients without DR or with NPDR. 20 In their study, the SUA levels of NPDR participants were significantly lower than those of participants without DR. 20 In our study sample, however, no significant difference was observed in SUA levels between patients with sub-VTDR and no DR.…”
Section: Discussionmentioning
confidence: 82%
“…In Chinese patients with T2DM, reduction in urinary uric acid excretion (UUAE) is an independent risk factor for DR [91]. Elevated SUA levels are significantly associated with albuminuria and DR severity [92], but not with the retinal nerve fibre layer or macular thickness [93]. A study reported that increased SUA levels were associated with an increased severity of DR in Taiwan [94].…”
Section: Epidemiology Studiesmentioning
confidence: 99%
“…Previous cross-sectional studies of the relationship between serum uric acid level and DR have provided mixed results. While Vinuthinee-Naidu et al showed that serum uric acid levels were not well-correlated to retinal nerve fibre layer and macular thickness among type 2 diabetic patients (Vinuthinee-Naidu et al, 2017) and older studies did not detect a relationship (Segato, 1991;Olukoga, 1991), other studies have shown that serum uric acid levels, diabetes and diabetic retinopathy are strongly correlated (Xia et al, 2014;Causevic et al, 2010). In our study, we found high uric acid levels in the PDR group.…”
Section: Discussionmentioning
confidence: 98%